The African human rights system, activist forces and international institutions / Obiora Chinedu Okafor. - Okafor, Obiora Chinedu (Cambridge University Press, 2007)
This 2007 book draws from and builds upon many of the more traditional approaches to the study of international human rights institutions (IHIs), especially quasi-constructivism. The author reveals some of the ways in which many such domestic deployments of the African system have been brokered or facilitated by local activist forces, such as human rights NGOs, labour unions, women's groups, independent journalists, dissident politicians, and activist judges. In the end, the book exposes and reflects upon the inherent inability of the dominant compliance-focused model to adequately capture the range of other ways - apart from via state compliance - in which the domestic invocation of IHIs like the African system can contribute - albeit to a modest extent - to the pro-human rights alterations that can sometimes occur in the self-understandings, conceptions of interest or senses of appropriateness held within key domestic institutions within states.